The Role and Importance of Culture and Art in The Development of Society - Yuldasheva Dilafruz Abdumalikovna (Zien Journals, 2021)
This article provides an overview of the role and importance of culture and art in the development of society, a brief overview of the attention paid to this area in our country, the formation and development of culture and art, as well as analytical reforms in this area. In the article you will also learn about the rich history of the emergence and development of culture and art, the author's suggestions and recommendations for the study
Keywords: Renaissance; art; Uzbek; culture